ANALISIS PENILAIAN KINERJA SUPPLIER PADA PT IDCSS - Riyan, Ian; Sumantika, Arsyad (Computer Science and Industrial Engineering, 2023)
The best performance assessment of suppliers in the company is an effort to improve the quality of service and provide the best products to customers. The effort aims to keep the company competitive by minimizing discrepancies in the supply chain flow. Research was conducted on PT IDCSS to find the best performing suppliers in meeting the needs of artificial ornamental plant products, to minimize problems arising from the supply of inappropriate products. The method used in this research is the VPI frame worked Analytical Hierarchy Process (AHP) method with the main criteria of Quality, Cost, Delivery, Flexibility and Response which are divided into 17 sub-criteria. The results showed that the highest weights were the delivery criteria (0.389), cost (0.294), quality (0.157), response (0.108) and flexibility (0.052). The assessment results on supplier performance supplier MIS (0.260), YOH (0.256), FYG (0.244), CIL (0.129) and supplier SAM (0.112). This shows that supplier MIS has the best performance as a supplier of artificial ornamental plant products for PT IDCSS.